Macro Comparisons in Max Weber’s Sociology: Precautions, Possibilities, Achievements, and Limitations - Kalberg, Stephen (Eurostudia, 2008)
AbstractMax Weber considers large-scale comparative study as an extremely delicate and complex endeavour. He insists on a certain number of precautions. According to him transcultural comparisons are definitely possible, but only in a specific and modest way. The present study will first present several major characteristics of sociology that render comparison difficult: we will stress its numerous reservations. We will then examine in which circumscribed manner the large-scale comparisons can be made, on the basis of ideal-types and their limited results.